Nursing Intervention of Red Ginger Warm Compress To Reduce Pain Levels In The Elderly - Erlinawati Dewi Hartoyo (Indonesian Journal of Community Development, 2023)
Background: Gout arthritis or often known by the public as uric acid is a degenerative problem that attacks the joints and is most often found in society, especially in the elderly. Often found complaints of joint pain in gout sufferers, the way to deal with pain is by warm compresses of red ginger. The goal is to reduce pain and improve blood circulation. Methods: Case study by providing nursing care to Mrs.S who is 60 years old with complaints of joint pain. Results: Based on a case study conducted by the author for 7 days, joint pain due to increased uric acid was reduced from pain scale 5 to scale 1. Conclusion: Giving red ginger warm compresses regularly can inhibit prostaglandin synthesis so as to reduce joint pain or tension muscle because it contains olerasin, namely gingerol, zingeron and shogaol.